Identification of Firefly Population Areas along Sepetang River Using the Buffer Method - Noor Fazeera, Ahmad Fuzi; Azimah, Abd Rahman (GEOGRAFI, 2024)
This study identifies firefly population areas along the Sepetang River using Geographic Information System (GIS) buffer analysis. The focus is on Pteroptyx tener, which thrives in mangrove ecosystems, especially around Sonneratia caseolaris (Berembang trees). Field data were collected over six months from ten stations along the river to analyze firefly abundance concerning surrounding land use and vegetation types. Buffer zones of 50, 100, and 150 meters were applied to assess the impact of environmental factors and human activities on firefly populations. The results revealed that Station 6 had the highest firefly concentration, attributed to its dense Berembang tree cover. These findings emphasize the significance of mangrove conservation for sustaining firefly habitats. This research highlights the effective use of GIS in ecological conservation and underscores the need for protective buffer zones to mitigate the impacts of urbanization on firefly populations.